An Investigation into Tetrodotoxin (TTX) Levels Associated with the Red Dorsal Spots in Eastern Newt (Notophthalmus viridescens) Efts and Adults. (2nd September 2018) - Spicer, Mackenzie M.; Stokes, Amber N.; Chapman, Trevor L.; Brodie, Edmund D.; Brodie, Edmund D.; Gall, Brian G.
Abstract : We investigated the concentration of tetrodotoxin (TTX) in sections of skin containing and lacking red dorsal spots in both Eastern newt ( Notophthalmus viridescens ) efts and adults. Several other species, such as Pleurodeles waltl and Echinotriton andersoni, have granular glands concentrated in brightly pigmented regions on the dorsum, and thus we hypothesized that the red dorsal spots of Eastern newts may also possess higher levels of TTX than the surrounding skin. We found no difference between the concentrations of TTX in the red spots as compared to neighboring skin lacking these spots in either efts or adults. However, efts with more red dorsal spots had elevated TTX levels relative to efts with fewer spots.